Increase of Production Efficiency of Tractor Part by Industrial Engineering Technique: A Case Study of Automotive Part Factory - Prasunjai, Anyarat; Vongpeng, Somporn (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this research is to increase production efficiency of tractor part RX 175-E. The study of production of RX 175-E was composed of three processes. The first process is the punching of a hole with a 74 millimeter diameter on the material. The second process is the punching for 12 holes with 13 millimeter diameter. The last process is the edge trimming with 200 millimeter diameter. Overall process was studied and analyzed problems by the manufacturing engineering such as production process chart, time study, flow chart, cause and effect diagram, ECRS concept, 5W 1H concept, PDCA concept and Kaizen. The maximum lead time occurs on the second process. This process was improved by modifying punch mold. The original punching could make 12 holes in 2 times and the new mold design can finish in one punch. From the improvement of the second process, the production can increase efficiency and decrease working steps. The processing time is reduced from the original production six seconds per part.